2005
DOI: 10.1145/1113847.1113888
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into student characteristics affecting novice programming performance

Abstract: Novice programmers usually experience difficulties when programming for the first time. The main aim of the study presented in this paper is to identify those characteristics that negatively effect procedural programming performance, so that additional support can be provided in the instruction of programming courses for students possessing these characteristics. Investigations were conducted at two South African tertiary institutions. At both institutions a first course in Java programming, focussing on proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
31
0
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 4 publications
8
31
0
5
Order By: Relevance
“…This could be due to the reason that the students understand the problem by translating the problem statement in English to their native language. The rules discovered in this study do confirm many findings from previous studies using non KDD approaches [17,18]. There is a positive correlation between the students' problem solving ability and their programming performance.…”
Section: Results and Rules Analysissupporting
confidence: 88%
“…This could be due to the reason that the students understand the problem by translating the problem statement in English to their native language. The rules discovered in this study do confirm many findings from previous studies using non KDD approaches [17,18]. There is a positive correlation between the students' problem solving ability and their programming performance.…”
Section: Results and Rules Analysissupporting
confidence: 88%
“…These results also confirm that abstract thinkers (convergers and assimilators) perform better in examination than concrete thinkers (accommodators and divergers). These results further support Allert [21]; Goold and Rimmer [48] and Pillay and Juggo [49] who stated that assimilators (abstract thinkers) did better than concrete thinkers. However, our results partially support Byrne and Lyons [50] who concluded that although learning style was not significant however, the convergers are the one who had selected the programming as a course of their study.…”
Section: Data Analysis and Resultssupporting
confidence: 87%
“…There are many individual characteristics [PJ05] [Ben05] that will impact how a programmer tackles a comprehension task. These differences also impact the requirements for a supporting tool.…”
Section: Programmer Characteristicsmentioning
confidence: 99%